PROSES PENYEMBUHAN GEJALA KEJIWAAN BERBASIS ISLAMIC INTERVENTION OF PSYCHOLOGY - Sumarni Sumarni (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2020)
This article examines the process of healing psychiatric symptoms through the intervention of Islamic psychology. According to data released by Riskesda in 2013, it shows that the prevalence of emotional mental disorders, as indicated by symptoms of depression and anxiety for the age of 15 years and over, reaches around 14 million people or 6% of the population of Indonesia while the prevalence of severe mental disorders, such as schizophrenia reaches around 400,000 people or as many as 1.7 per 1,000 population this shows how the level of depression in Indonesia is very high and requires serious treatment. This article uses a type of research based on literature studies conducted through data collection and documentation, with analysis techniques using data reduction and drawing conclusions and through the praxis of literature ranging from books, scientific journals, e-books, the internet and various available facts, results and discussion that Islamic psychotherapy is considered capable of being used as one of the most effective therapies for psychological disorders in a client. The purpose of psychotherapy alone is to improve the quality of human life both physically and psychologically, so as to reduce the high level of anxiety to have a calm feeling in the presence of God as a giver of healing. The therapy is divided into several types of therapy including worship-based therapy and moral-based therapy. Worship-based therapy includes dhikr, prayer, reading / understanding of the Qur'an, prayer, fasting, almsgiving, and pilgrimage. Moral-based therapy that is sincere, happy, thankful, qanaah, patient, forgiving, husnudzon, tawakal, muhasabah, and tafakur.